Role of matrix metalloproteinase 7 in ovarian cancer (review of literature) - R. I. Knyazev; I. I. Bokin; V. V. Barinov (ABV-press, 2015)
Ovarian carcinoma is one of the most aggressive cancer in women, and one of the leading causes of death from cancer of the reproductive system. Despite enhancement methods of prevention, early diagnosis, treatment, such as surgery, radiation, drugs, including targeted and hormone therapy, long-term results remain unsatisfactory. In this connection, much attention is paid to the search for molecular biological mechanisms involved in carcinogenesis and the development of laboratory tests for detecting patients at early stages of tumor process, to differentiate malignant and benign tumors, to determine the tactics of treatment of a particular patient, to assess the prognosis. One of the key aspects of the pathogenesis of ovarian cancer is the interaction of tumor tissue extracellular matrix, the protein degradation of which in most cases is controlled by proteolytic enzymes. Matrix metalloproteinase 7 (MMP-7), also known as matrilysin, like other members of the matrix metalloproteinase` family, demonstrates proteolytic activity against components of the extracellular matrix, the degradation of which is the basis of cancer invasion and metastasis. Matrilysin is also involved in the regulation of activities of bioactive molecules associated with cell physiology. The overview briefly highlights the role of MMP-7 in ovarian cancer.